ANALISIS KEPUTUSAN PETANI DALAM USAHATANI PADI ORGANIK DAN PADI ANORGANIK DI LAHAN IRIGASI KECAMATAN BELITANG III KABUPATEN OGAN KOMERING ULU TIMUR - Trinawati; Maryadi; Adriani, Dessy (Agripita Publisher, 2018)
The purpose of this study was: 1) to describe the differences in cultivation techniques of organic and anorganic rice farming in Irrigated land, Belitang III District, Ogan Komering Ulu Timur, 2) to analyze the productivity and farm revenue of organic and anorganic rice farming in Irrigated land, Belitang III District, Ogan Komering Ulu Timur, 3) to analyze factors that influence farmers decision in organic and anorganic rice farming in irrigated land, Belitang III District, Ogan Komering Ulu Timur. The data collection was conducted during December 2016. The research method was a survey, which the rice farmers of organic and anorganic as the study sample. Samples of farmers were 30 farmers of organic rice and 30 of anorganic rice farmers where they are members of a farmers' group called